Acute Postnatal Ablation of Hif-2α Results in Anemia - Gruber, Michaela; Hu, Cheng-Jun; Johnson, Randall S.; Brown, Eric J.; Keith, Brian; Simon, M. Celeste (Proceedings of the National Academy of Sciences - PNAS, 2007)
Adaptive transcriptional responses to oxygen deprivation (hypoxia) are mediated by the hypoxia-inducible factors (HIFs), heterodimeric transcription factors composed of two basic helix-loop-helix-PAS family proteins. The transcriptional activity of HIF is determined by the hypoxic stabilization of the HIF-α proteins. HIF-1α and HIF-2α exhibit high sequence homology but have different mRNA expression patterns; HIF-1α is expressed ubiquitously whereas HIF-2α expression is more restricted to certain tissues, e.g., the endothelium, lung, brain, and neural crest derivatives. Germ-line deletion of either HIF subunit is embryonic lethal with unique features suggesting important roles for both HIF-α isoforms. Global deletion of Hif-2α results in distinct phenotypes depending on the mouse strain used for the mutation, clearly demonstrating an important role for HIF-2α in mouse development. The function of HIF-2α in adult life, however, remains incompletely understood. In this study, we describe the generation of a conditional murine Hif-2α allele and the effect of its acute postnatal ablation. Under very stringent conditions, we ablate Hif-2α after birth and compare the effect of acute global deletion of Hif-2α and Hif-1α. Our results demonstrate that HIF-2α plays a critical role in adult erythropoiesis, with acute deletion leading to anemia. Furthermore, although HIF-1α was first purified and cloned based on its affinity for the human erythropoietin (EPO) 3′ enhancer hypoxia response element (HRE) and regulates Epo expression during mouse embryogenesis, HIF-2α is the critical α isoform regulating Epo under physiologic and stress conditions in adults.